Bacterial Evasion of Host Antimicrobial Peptide Defenses - Cole, Jason N. (Microbiol Spectr, 2016)
Antimicrobial peptides (AMPs), also known as host defense peptides, are small naturally occurring microbicidal molecules produced by the host innate immune response that function as a first line of defense to kill pathogenic microorganisms by inducing deleterious cell membrane damage. AMPs also possess signaling and chemoattractant activities and can modulate the innate immune response to enhance protective immunity or suppress inflammation. Human pathogens have evolved defense molecules and strategies to counter and survive the AMPs released by host immune cells such as neutrophils and macrophages. Here, we review the various mechanisms used by human bacterial pathogens to resist AMP-mediated killing, including surface charge modification, active efflux, alteration of membrane fluidity, inactivation by proteolytic digestion, and entrapment by surface proteins and polysaccharides. Enhanced understanding of AMP resistance at the molecular level may offer insight into the mechanisms of bacterial pathogenesis and augment the discovery of novel therapeutic targets and drug design for the treatment of recalcitrant multidrug-resistant bacterial infections.